A vision on the opportunities, policies and coping strategies for the energy security and green energy development in Malaysia. (November 2015) - Foo, K.Y.
Abstract: Energy security management remains a complex and fragmented interplay between the population growth, urbanization, economical development and the living environment. Today, green technology application has been the prime contributor and an indispensable factor to preserve the long term reliability of energy supply. This agenda has called for an integrated, adaptive, coordinated, environmentally-oriented and participatory approach to the protection of renewable resources. Malaysia, endowed with its rich natural resources and diversity recognizes the need to adopt a sound developmental framework to transform the country׳s energy management landscape into a high quality and excellent level. Parallel to this development, both government and non-governmental organizations continue to advocate national efforts to explore alternative energy, and improve the dynamic energy growth in a cost-effective manner. The plan espouses the establishment of ocean energy, geothermal power, hydropower, wind power, hydrogen fuel cell, nuclear energy, biodiesel and bioethanol processing industries. The impetus is accompanied by the integration of environmental protection rules and boosted by the implementation of new energy policies. The present work attempts to address the opportunities, dynamic pressure, and coping strategies of energy security, and green energy development in Malaysia. The present and future outlooks of renewable and non-renewable energy are elucidated. Besides, the research breakthroughs and joint co-operations for the promotion of green energy management are outlined.